Wage and employment effects of immigration to Germany: an analysis based on local labor markets - Jörn-Steffen Pischke; Johannes Velling (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1994)
We analyze the impact of increased immigration on labor market outcomes of natives in Germany using a dataset of county level variables for the late 1908s. In order to construct more unified labor market regions we aggregate the 328 counties to 167 larger regions. We study two measures of immigration, the change in the share of foreigners between 1985 and 1989 as well as one year gross and net flows of immigrants to an area. In order to address the potential problem of immigrant selection into local labor markets with superior performance we instrument the change in the foreign share by its previous level. Especially for unemployment we find large effects of an increased foreign share. We conjecture that these results might be spurious. Foreigners tend to be concentrated in lower unemployment areas but unemployment tends to be mean reverting during the boom period we study. This leads to a positive correlation between the instrument and the change in unemployment. Taking account of the mean reversion in unemployment we find no detrimental effect of immigration. Similar results are obtained on the basis of one year flow data of foreigners. We also find no support for the hypothesis that the absence of displacement effects are due to a response of native migration patterns. The initial settlement of immigrants in Germany is largely independent of labor market conditions. Subsequent internal moves by foreigners are more responsive to local unemployment albeit much less than internal migration of natives.
Keywords: 330